ORTHOPAEDIC IMPLANT: A COMPREHENSIVE STUDY OF ASSOCIATED RISK FACTORS - Aggarwal, Manvi; Thakkar, Arti; Sinha, Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction-Orthopaedic technology plays a significant role, including anything from entirely spinal systems to joint restoration. These devices are often composed of metal, ceramic, or polymer. Orthopaedic surgery has helped millions of patients by restoring their mobility, relieving their pain, and ultimately improving their quality of life. But their high risk of adverse effects such as device breakage, surgical site infections, discomfort, edema, and so forth limited their utilization. So, the primary objective of the current study is to estimate the prevalence of adverse events after orthopaedic implantation. Methodology- A meta-analysis was conducted on adverse effects of orthopaedic implantation, examining 151 case studies started from year 2000 to 2022, using the Medline, Embace, and Google Scholar databases. The review focused on factors like implant type, patient age, gender, reaction start time, adverse events, clinical presentation, and results. Result and Discussion- Research verified that male patients experience more adverse effects from orthopaedic implants due to increased BMI, which strains the implants. Lower limb surgery is more common due to weight-bearing implants. Common adverse reactions include metallosis, fracture, and infection. An accumulation of metal ions in the bloodstream causes the implant to become loose, induce inflammatory responses, and cause chronic pain around the implant site. Conclusion- Factors like implant quality, selection, fixation, fracture geometry, and postoperative care can lead to implant failure. Age and gender should be considered during preoperative planning and postoperative care. Traditional Polyethylene bearing surfaces are suitable for older patients. Patients should receive counselling, informed about implant options, and given weight bearing instructions.